Changes in thyroid function after thermal ablation of thyroid nodules - Li, Song; Yu, Ming-an; Zhao, Zhen-long; Wei, Ying; Peng, Li-li; Li, Yan (Frontiers in Endocrinology, 2025)
PurposeTo evaluate changes in thyroid function post-thermal ablation (TA) of thyroid nodules and to identify risk factors associated with post-ablation thyroid function abnormalities.Materials and methodsA retrospective analysis of 2,264 cases treated with TA between June 2015 and July 2024 was conducted, including 1,169 benign thyroid nodules (BTNs) and 1,095 papillary thyroid carcinoma (PTC) cases. Thyrotropin (TSH), free triiodothyronine (FT3), and free thyroxine (FT4) levels were measured before treatment and at 1, 3, 6, 9, and 12 months post-ablation.ResultFT3 levels remained significantly reduced at 12 months post-ablation (3.04 ± 0.42 vs. 3.15 ± 0.36 pg/mL; p < 0.001). In contrast, FT4 levels showed a persistent increase at 12 months (1.36 ± 0.69 vs. 1.27 ± 0.15 ng/dL; p < 0.001). Although TSH levels decreased slightly over time, they remained elevated at 12 months compared to baseline (1.80 ± 1.17 vs. 1.73 ± 0.84 μIU/mL; p = 0.029). At the end of the follow-up period, the incidence of thyroid function abnormalities was 5.07% (18/355), with only one patient requiring Thiamazole for antithyroid therapy. The cumulative incidence of thyroid function abnormalities was notably higher in the PTC group compared to the BTN group (17.80% vs. 10.94%; p < 0.001). Pre-ablation TSH levels (OR= 2.06; 95% CI, 1.77–2.39; p < 0.001), Hashimoto’s thyroiditis (OR = 2.66; 95% CI, 1.88–3.77; p < 0.001), and multiple nodules were positively correlated with the occurrence of thyroid function abnormalities. The cutoff value of TSH was 2.015 μIU/mL with a sensitivity of 0.527 and a specificity of 0.246 (AUC = 0.625).ConclusionThermal ablation had a minimal impact on thyroid function. Pre-ablation TSH levels, Hashimoto’s thyroiditis, and multiple nodules were risk factors for post-ablation thyroid function abnormalities.